Implementation of Quality Management with a Special Job Fair Program at SMKN Purwosari Bojonegoro - Frensi Agustina; Maria Veronica Roesminingsih; Tri Retno Hariastuti (Al Hikmah: Journal of Education, 2023)
This study aims to find out and describe how the implementation of quality management with a special job fair program at SMKN Purwosari Bojonegoro. The research method used is descriptive qualitative research. Data were collected using in-depth interviews, participant observation, documentation and field notes. Data analysis techniques include three stages, namely data condensation, data presentation and data verification. Data validity criteria include credibility with triangulation of techniques and sources, dependability, confirmability and transferability. The results of this study are that quality management with a special work program at Purwosari Vocational High School has been carried out properly, systematically, clearly and measurably by the school principal, head of the BKK program and school members. The results of this study indicate that the school has done well: 1) Planning BKK work programs, 2) Guidance and counseling programs for prospective graduates in preparation for the world of work, 3) Establishing cooperation with the business world and the industrial world as job users, 4) Absorption graduates in the world of business and industry, 5) Special job market job programs lead to linearity of graduates' competencies in the world of work